Ethical sensitivity of accounting students: evidence from Malaysia - Nadaraja, Suba Ranjini; Mustapha, Mazlina (Econjournals, 2017)
The goals of ethics education include the fostering of awareness about ethical components in managerial decision making and assist the students to apply ethical analysis to daily business activities. It is claimed that the inclusion of ethics in accounting curriculum can give students guidance as to how to deal with the real business situations. This paper investigates the importance of ethical sensitivity of accounting students and how ethics education would affect them. Specifically, it attempts to examine how attending ethic classes would affect their decision making. Questionnaires were distributed to 114 final year accounting students at the beginning of the semester (pre) and at the end of the semester (post). Interviews were also conducted to understand the issues of the study. Paired sample t-tests were employed to analyze the data. The results appear to suggest that the final year accounting students understand the importance of ethics in general. The paired sample t-tests results show that after attending the ethic classes, their ethical sensitivity improved. However, when they were given some ethical situations to assess, the students indicated that they possessed moderate ethical sensitivity for both pre and post results.